2021
DOI: 10.1111/jocd.14216
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Dimensional Aesthetic Scan Assessment (MD ASA™): Initial experience with a novel consultation, facial assessment, and treatment planning tool

Abstract: Background: Comprehensive patient assessment and planning are central to esthetic treatment with injectables. MD ASA™ (Multi-Dimensional Aesthetic Scan Assessment) is a novel tool developed for this purpose. Aims:To describe the MD ASA technique and present its preliminary application.Methods: MD ASA breaks down the face into five hierarchies (H1-H5). H1 shifts patients' focus from "distractions" (individual lines and folds) toward the overall messages their face portrays, based on eight Emotional Attributes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…10 11 12 The aging process may produce a sad look when the patient is not feeling sad which means that unfavorable facial signs may lead to discrepancy between feelings and physical appearance. 8…”
Section: Emotional Attributesmentioning
confidence: 99%
See 3 more Smart Citations
“…10 11 12 The aging process may produce a sad look when the patient is not feeling sad which means that unfavorable facial signs may lead to discrepancy between feelings and physical appearance. 8…”
Section: Emotional Attributesmentioning
confidence: 99%
“…The suggested equations for the treatment of the negative Emotional Attributes were already published in another paper. 8 On the other hand, there are four positive or favorable facial messages that patients usually desire to convey and are considered to be the “dreams.” Here are included patients' requests such as to achieve a more attractive, younger, more contoured or a more feminine/masculine look. The 7-point Shape and The 9-point Shape are technical options to directly improve the saggy appearance and indirectly the tired look, sad look and angry look (negative attributes).…”
Section: Emotional Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found that aging patients are commonly concerned with one area, such as nasolabial folds, without being aware of underlying or causative aging changes such as volume loss elsewhere, even when using a mirror. 6 Many patients have limited knowledge of either contributory aging factors or negative nonverbal messages communicated by the face. Should they attribute their negative feelings to one specific feature, discussion prior to treatment is needed to set realistic expectations around their presenting concern.…”
Section: Discussionmentioning
confidence: 99%